Biogas production from waste : Technical overview, progress, and challenges - Ghosh, Pooja; Shah, Goldy; Sahota, Shivali; Singh, Lakhveer; Vijay, Virendra Kumar (Elsevier, 2020)
With the depletion of fossil fuels, growing energy demands, and the issue of climate change, finding sustainable renewable sources of energy has become extremely important. Innovative approaches are being developed for the production of bioenergy, biomaterials, and chemicals from organic wastes so as to find an alternative to fossil fuels as well solve the problem of the dumping of organic wastes into landfills. One viable options of energy generation from organic wastes is biogas. An added advantage of biogas technology is the production of organic manure for crops. This chapter is intended to evaluate the current status of biogas production, the various feedstocks available, the technological advancements being made, and the barriers in the dissemination of these technologies.